Pericardial Hydatidosis Revealed by Tamponade, A Case Report - Abdelbaki, Mourad; Khellafi, Dr N. (International Journal of Innovative Research in Medical Science, 2024)
Hydatidosis or hydatid cyst is a Cosmopolitan Zoonosis, due to accidental tissue development in humans of the Taenia Echinococcus granulosus larva, an adult parasite of the small intestine of dogs. Very widespread in Mediterranean countries, where it is generally maintained through a domestic cycle involving dogs and sheep. Algeria is a country with high endemicity, and parasitosis constitutes a major health problem. Pericardial localization without cardiac involvement is extremely rare. We report the observation of isolated intrapericardial hydatidosis revealed by tamponade.